Prenatal intervention in high-risk CPAM: postnatal outcomes after fetal versus standard surgery : a propensity score matched study - Klinke Petrowsky, Michaela; Elrod, Julia; Martel, Richard; Schaible, Thomas; Nientiedt, Tobias; Boettcher, Johannes; Kohl, Thomas; Boettcher, Michael (European journal of pediatric surgery, 2025)
Congenital pulmonary airway malformation (CPAM) is a rare fetal lung anomaly characterized by cystic lesions that can impede lung development. While smaller lesions may remain asymptomatic and are managed postnatally, larger lesions can cause severe complications such as mediastinal shift and hydrops fetalis. Fetal surgery may be indicated in these cases. This study analyzed whether fetal surgical intervention affects outcomes of subsequent postnatal surgery in CPAM patients. A retrospective single-center cohort study was conducted on pediatric patients treated for CPAM between January 2010 and August 2024. Patients were divided into two groups: those with prenatal surgical intervention and those treated with postnatal surgery only. Propensity score matching based on gestational age, gender, birth weight, and lesion volume ratio yielded 23 matched patients: 14 in the fetal surgery group and 9 in the control group. Baseline characteristics, type of fetal intervention, intraoperative, and long-term postoperative outcomes were assessed. Multivariable regression was performed to account for confounding variables. Among 179 identified patients, 23 were included after propensity score matching: 14 in the fetal surgery group and 9 in the standard postnatal surgery group. Baseline characteristics were balanced, except for significantly higher disease severity in the fetal surgery group (hydrops 69% vs. 0%, p < 0.001; mediastinal shift 93% vs. 33%, p = 0.001). Alcohol ablation was the most common fetal intervention; however, various other prenatal procedures were also performed, with most patients undergoing multiple interventions. Tendencies but no significant differences were found in primary outcomes, including mortality (15% vs. 0%, p = 0.26) and recurrence (29% vs. 0%, p = 0.18). Secondary outcomes such as ventilation duration and intensive care stay were longer in the fetal surgery group, but not statistically significant. Despite higher baseline disease severity, patients who underwent fetal intervention showed postnatal outcomes comparable to those with less severe CPAM. Fetal surgery did not appear to adversely affect surgical recovery. These findings should be interpreted with caution but may support the selective use of prenatal intervention in high-risk cases and underscore the need for further research to refine both prenatal strategies and postnatal care.